Cecropin A Alleviates Inflammation Through Modulating the Gut Microbiota of C57BL/6 Mice With DSS-Induced IBD - Zhai, Zhenya; Zhang, Fan; Cao, Ruihua; Ni, Xiaojun; Xin, Zhongquan; Deng, Jinping; Wu, Guoyao; Ren, Wenkai; Yin, Yulong; Deng, Baichuan (Frontiers in Microbiology, 2019)
The present study is undertaken to assess the alleviating effects of antimicrobial peptide cecropin A on inflammatory bowel disease (IBD) in C57BL/6 mice and changes in the gut microbiota, compared to an antibiotic gentamicin. Different doses of cecropin A were intraperitoneally injected into C57BL/6 mice for 5 days to determine the safe doses. The injection doses at ≤ 15 mg/kg showed no negative impact on the liver, heart, spleen and kidney. The severe and moderate IBD mice model was successfully established via supplementation of 4% or 2.5% dextran sulfate sodium (DSS) in drinking water for 5 days. The severe IBD model was used to ensure the optimal therapeutic dose of cecropin A. Survival rate, body weight and disease activity index (DAI) scores were measured. Administration of 15 mg/kg, not 5 mg/kg cecropin A, for 5 days increased survival rate and decreased body weight loss of mice. The moderate IBD model was applied to investigate the mechanisms for cecropin A to alleviate inflammation in comparison to gentamicin. The mice were treated with 15 mg/kg cecropin A or 5 mg/kg gentamicin for 3 days. The levels of cytokines and related proteins in the colon were detected by ELISA and Western blotting. The microbiota in cecum contents were analyzed using 16S rRNA gene sequencing. The results showed that cecropin A and gentamicin relieved body weight loss, DAI, and gut mucosa disruption, while decreasing tumor necrosis factor-α (TNF-α), interlukin-1β (IL-1β) and interlukin-6 (IL-6) induced by DSS. In addition, cecropin A and gentamicin showed different effects on the gut microbiota structure. Both cecropin A and gentamicin decreased DSS-induced enrichment of Bacteroidaceae and Enterobacteriaceae. However, cecropin A showed a selective enrichment of Lactobacillus in contrast to gentamicin, which demonstrated a selective effect on Desulfovibrionaceae and Ruminococcaceae. Cecropin A alleviates IBD through decreasing harmful gut microflora and specifically enhancing beneficial gut microflora. The mechanism of this effect is different from gentamicin.